Dynamics of Human Mesenchymal Stem Cells, M1 Microglia/Macrophage, and Fractalkine in Ischemic Stroke Patients - Herminawati, Lucia; Wijaya, Andi; Arief, Mansyur; As’ad, Suryani (BALI MEDICAL JOURNAL; Vol 5 No 1 (2016), 2016)
Background: About 85% of strokes are ischemic strokes, caused by occlusion of cerebral artery that induced brain inflammation. A deep understanding of ischemic stroke mechanism will lead to better neurorestorative treatment. Objective: This study investigates the dynamics of human mesenchymal stem cells, fractalkine, and M1 microglia/macrophage in ischemic stroke patients. Results: We found the same fractalkine levels and M1 microglia/macrophage cells on patients with stroke onset 0 to 14 days, then decrease until 30 days of stroke onset. MSCs was increase 7 days after stroke onset, peaked by 14 days, then decreased until 30 days after stroke ischemic onset. Conclusions: This study found an interaction between microglia/macrophage, fractalkine, and MSCs on ischemic stroke patients, so therapeutic strategy could be developed.
Keywords: ischemic stroke, microglia, fractalkine, mesenchymal stem cells